Chalcone Attenuates Staphylococcus aureus Virulence by Targeting Sortase A and Alpha-Hemolysin - Zhang, Bing; Teng, Zihao; Li, Xianhe; Lu, Gejin; Deng, Xuming; Niu, Xiaodi; Wang, Jianfeng (Frontiers in Microbiology, 2017)
Staphylococcus aureus (S. aureus) resistance, considered a dilemma for the clinical treatment of this bacterial infection, is becoming increasingly intractable. Novel anti-virulence strategies will undoubtedly provide a path forward in combating these resistant bacterial infections. Sortase A (SrtA), an enzyme responsible for anchoring virulence-related surface proteins, and alpha-hemolysin (Hla), a pore-forming cytotoxin, have aroused great scientific interest, as they have been regarded as targets for promising agents against S. aureus infection. In this study, we discovered that chalcone, a natural small compound with little anti-S. aureus activity, could significantly inhibit SrtA activity with an IC50 of 53.15 μM and Hla hemolysis activity with an IC50 of 17.63 μM using a fluorescence resonance energy transfer (FRET) assay and a hemolysis assay, respectively. In addition, chalcone was proven to reduce protein A (SpA) display in intact bacteria, binding to fibronectin, formation of biofilm and S. aureus invasion. Chalcone could down-regulate the transcriptional levels of the hla gene and the agrA gene, thus leading to a reduction in the expression of Hla and significant protection against Hla-mediated A549 cell injury; more importantly, chalcone could also reduce mortality in infected mice. Additionally, molecular dynamics simulations and mutagenesis assays were used to identify the mechanism of chalcone against SrtA, which implied that the inhibitory activity lies in the bond between chalcone and SrtA residues Val168, Ile182 and Arg197. Taken together, the in vivo and in vitro experiments suggest that chalcone is a potential novel therapeutic compound for S. aureus infection via targeting SrtA and Hla.